The Mediterranean sheep and goat sectors between constants and changes over the last decade Future challenges and prospects - Dubeuf J.-P.; Aw-Hassan A.; Chentouf M.; Mena Y.; Pacheco F.; Boutonnet J.P. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The overview of the sheep and goat sectors around the Mediterranean Basin shows permanent and common traits and these sectors have always a peculiar importance. But drastic changes have been observed for the last decade with a decreasing share of sheep and goat meat supply with new trends in marketing. The sheep and goat milks play always a significant role in the region but with changes in the demand of consumers and a growing demand for goat milk products. But the future of these sectors cannot be explored only through the markets and the consumers’ behaviours which have to be connected to the farmers’ decision processes and the social and economic situation of the hinterlands. The pastoral components of the production systems appear to be a good lever to prospect their futures. The remuneration of ecosystemic services (to prevent fire, protect bio-diversity, and preserve landscapes, for instance), the enhancement of agro-ecological characteristics of pastoral systems and products (based on local breeds, use of natural feeding resources, local marketing on short chains...), the certification and labelling of pastoral products in relation to the other activities of the territories are all possible ways to improve the value chains of sheep and goats. In all cases, the improvement of the information systems for these pastoral sectors, the reorganization of training programs and implementation of more efficient extension services is necessary to concretize these outlooks and depends of the internal dynamics, choices and balances of powers within each territory.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)